2017
DOI: 10.21315/mjms2017.24.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Interference Effect of Prior Explicit Information on Motor Sequence Learning in Relapsing-Remitting Multiple Sclerosis Patients

Abstract: Original Article Abstract Background: Multiple sclerosis (MS) is the most widespread disabling neurological condition in young adults around the world. The purpose of this study was to investigate the impact of explicit information (EI) on motor-sequence learning in MS patients.Methods: Thirty patients with relapsing-remitting MS (RRMS), age: 29.5 (SD = 5.6) years and 30 healthy gender-, age-, and education-matched control group participants, age: 28.8 (SD = 6.0) years, were recruited for this study. The parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
1
6
1
Order By: Relevance
“…Although conventional MRI sequences are not successful in cortical lesions demonstration, and despite the advances in new MR techniques such as magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI), still conventional MRI protocols playing an important role in early diagnosis of MS or CIS (suggestive of MS) [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conventional MRI sequences are not successful in cortical lesions demonstration, and despite the advances in new MR techniques such as magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI), still conventional MRI protocols playing an important role in early diagnosis of MS or CIS (suggestive of MS) [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an autoimmune inflammatory disease of the central nervous system (CNS), resulting to neurological disorder in both the youth and the elderly in the worldwide and accounts for about 1.5% of neurological abnormalities, associated with a progressive physical damage [1,2]. The disease affects the calloso-septal interface, periventricular white matter, cerebellum, and brain stem [3,4]. Several studies revealed that most MS lesion load histologically are on the cerebral cortex specifically the gray matter and white mater interface [5], which commonly associated with cognitive disability which can be revealed by magnetic resonance imaging (MRI) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence learning has occurred when reaction times and/or errors are decreased in the repeated sequences as compared with random stimuli. 23,24 Studies comparing motor sequence learning in upper-limb tasks between pwMS and healthy adults indicated, in general, similar performance improvements during implicit conditions, but reduced improvements under explicit conditions, 12,13,[17][18][19] although contrastingly Tacchino et al reported no improvements for pwMS in the implicit condition, while healthy adults did improve. 21 Furthermore, only four studies examined both implicit and explicit learning conditions within pwMS, and contrasting results were reported on differences between those conditions in pwMS, with two studies reporting less learning in explicit conditions 17,18 and two in implicit conditions.…”
Section: Introductionmentioning
confidence: 98%
“…23,24 Studies comparing motor sequence learning in upper-limb tasks between pwMS and healthy adults indicated, in general, similar performance improvements during implicit conditions, but reduced improvements under explicit conditions, 12,13,[17][18][19] although contrastingly Tacchino et al reported no improvements for pwMS in the implicit condition, while healthy adults did improve. 21 Furthermore, only four studies examined both implicit and explicit learning conditions within pwMS, and contrasting results were reported on differences between those conditions in pwMS, with two studies reporting less learning in explicit conditions 17,18 and two in implicit conditions. 12,21 However, in pwMS, motor impairments in walking and balance are prevalent, and it is unknown whether the findings on motor sequence learning from the abovementioned upper-limb tasks generalize to motor tasks involving dynamic balance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation